THE PROSPECT OF SOLAR POWER GENERATION TECHNOLOGY - C., Ajaegbu; O., Awodele; Kuyoro, Afolashade; A. A., Omotunde (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Over the years, several means of electrical power generation have been in place ranging from wood, coal, to fuel. All these means have at its point served purpose at the needed time. This work presents the historical research of solar power in space, an insight into some literature pertaining to Solar Power Satellite (SPS) and Wireless Power Transmission (WPT) and an insight into the working principle of solar power generation was presented. It was observed that despite the various prospects that were identified by the various researchers less attention was paid to the means of enhancing the range of transmission of solar power satellite